Comparison between use of a pleural drainage system with flutter valve and a conventional water-seal drainage system after lung resection: a randomized prospective study - Souza, Rodrigo Caetano de; Morais, Lilianne Louise Silva de; Ghefter, Mario Claudio; Franceschini, Juliana Pereira; Pinto, Fernando Campos Gomes (São Paulo Medical Journal, 2025)
BACKGROUND: There is still a debate regarding the most appropriate pleural collector model to ensure a short hospital stay and minimum complications. OBJECTIVE: To study aimed to compare the time of air leak, time to drain removal, and length of hospital stay between a standard water-seal drainage system and a pleural collector system with a unidirectional flutter valve and rigid chamber. DESIGN AND SETTING: A randomized prospective clinical trial was conducted at a high-complexity hospital in São Paulo, Brazil. METHODS: Sixty-three patients who underwent open or video-assisted thoracoscopic lung wedge resection or lobectomy were randomized into two groups, according to the drainage system used: the control group (WS), which used a conventional water-seal pleural collector, and the study group (V), which used a flutter valve device (Sinapi® Model XL1000®). Variables related to the drainage system, time of air leak, time to drain removal, and time spent in hospital were compared between the groups. RESULTS: Most patients (63%) had lung cancer. No differences were observed between the groups in the time of air leak or time spent hospitalized. The time to drain removal was slightly shorter in the V group; however, the difference was not statistically significant. Seven patients presented with surgery-related complications: five and two in the WS and V groups, respectively. CONCLUSIONS: Air leak, time to drain removal, and time spent in the hospital were similar between the groups. The system used in the V group resulted in no adverse events and was safe. REGISTRATION: RBR-85qq6jc (https://ensaiosclinicos.gov.br/rg/RBR-85qq6jc).